Pengaruh Good Corporate Governance Dan Islamic Corporate Social Responsibility Terhadap Profitabilitas (Roa) Pada Bank Umum Syariah Di Indonesia Tahun 2017-2020 - Ami Mastura; Ambok Pangiuk; Refky Fielnanda (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis aims to determine the Effect of Good Corporate Governance and Islamic Corporate Social Responsibility on Profitability (ROA) in Islamic Commercial Banks in Indonesia in 2017-2020. This study uses the independent variable, namely Good Corporate Governance with the proxy of the Board of Commissioners, Board of Directors and Islamic Corporate Social Responsibility. The dependent variable is Profitability (ROA). The data used in this study is secondary data, namely the annual report and the GCG report of Islamic Commercial Banks for the 2017-2020 period. The population in this study are all Islamic Commercial Banks registered with the Financial Services Authority in the 2017-2020 period. The sample was selected by purposive sampling method and 8 samples were obtained. The analytical method used in this research is panel data regression, model testing, classical assumption test, t test, and f test which are processed using the Eviews 8 application and Microsoft Excel 2010. The results of this study indicate that the board of commissioners has no effect on profitability (ROA) at Islamic Commercial Banks in Indonesia in 2017-2020. The board of directors has no effect on the profitability (ROA) of Islamic Commercial Banks in Indonesia in 2017-2020. Islamic Corporate Social Responsibility has no effect on profitability (ROA) at Islamic Commercial Banks in Indonesia in 2017-2020. The board of commissioners, board of directors, Islamic Corporate Social Responsibility simultaneously (simultaneously) affect the profitability (ROA) of Islamic Commercial Banks in Indonesia in 2017-2020.